Cara and MacRae's psychosocial occupational therapy : an evolving practice - MacRae, Anne; Cara, Elizabeth (Thorofare, NJ : Slack Incorporated, 2019)
'This text is designed to meet practice challenges as the occupational therapy profession continues to evolve to meet the current needs of our communities. Section I addresses practice settings and service delivery, with an emphasis on describing the entire continuum of health, social service, and community settings and how psychosocial occupational therapy is valuable in all settings. New to this book is the exploration of models of integrated primary care and the emergence of an occupational therapy presence in primary care, especially suited for occupational therapists because of our generalist background. Section II provides a greater emphasis on understanding the person in multiple contexts. The cultural and environmental content found in previous editions is expanded into two chapters, and there is a new chapter discussing personal and social identity. This new chapter explores the personal and social interrelatedness of stigma and dimensions of identity. Although trauma awareness and trauma-informed care are discussed throughout this book, it is in this chapter that the trauma-related issues of poverty, violence, and human displacement are discussed, as well as the role of occupational therapy in all issues presented. Section III maintains a much-heralded section of the previous editions--Mental Health Across the Lifespan--now expanded to include new chapters on the mental health of emerging adults and mid-life adults. The expansion of this part of the book is designed to allow a more thorough examination of lifespan issues. However, readers are urged to keep in mind that defining lifespan stages is a somewhat arbitrary concept based on chronology alone'--Provided by publisher.
Preceded by Psychosocial occupational therapy : an evolving practice / Elizabeth Cara, Anne MacRae. 3rd ed. c2013.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072, 650 - OCLC control number change
Keywords: Occupational Therapy -- methods; Mental Disorders -- rehabilitation; Occupational therapy -- Methods; Mental illness -- Rehabilitation; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine